Entanglement between visitor and attractions through sensory experiences perspective in the context of cultural heritage tourism - Ismail, Hairul Nizam (2015)
Automotive industry has become one of the most contributing industries to an economy, including Indonesia. Therefore, factors affecting it are carefully being identified. In this quantitative study, the researcher would like to analyze the influence of several economic factors. There are crude oil price, consumer confidence, exchange rate and gros domestic bruto (GDP) growth rate toward sales number of automotive industry. In this study, the researcher uses case study of PT. Toyota Astra Motor (PT. TAM) as representative from Indonesia’s automotive industries. The total observation is 84 observations, derived from 7 years on monthly basis. This research uses multiple regression analysis to analyze the influence. The result of this study is that crude oil price, consumer confidence, exchange rate and GDP growth rate have positive significant influence toward sales number altogether. The most significant factor is exchange rate. All of the factors are found out to influence sales number by 78.8% while other remaining 21.2% of sales number is influenced by other factors outside the regression model.